Evaluating Zoysiagrass-Tall Fescue Mixtures in Kansas - Mingying Xiang; J. Fry; M. Kennelly (Kansas Agricultural Experiment Station Research Reports, 2017)
Water conservation is increasingly important when selecting turfgrasses. Zoysiagrass (Zoysia japonica), a C4 grass, is more drought resistant than C3 grasses. However, there is some resistance to the use of zoysiagrass in lawns and golf courses due to its extended dormant period when turf is brown. The objective of this study was to evaluate mowing height, tall fescue seeding rate and time for establishment of a mixed stand with seeded zoysiagrass. Seeding zoysiagrass and tall fescue together in June generally resulted in a less uniform mixture than seeding zoysiagrass in June and then seeding tall fescue in September. Tall fescue seeded in September at 8 lb pure live seed/1,000 ft2resulted in the most uniform mixture of the two species.
Keywords: Turfgrass; ecology; management